2016
DOI: 10.1167/iovs.16-19578
|View full text |Cite
|
Sign up to set email alerts
|

Glaucoma Diagnostic Ability of the New Circumpapillary Retinal Nerve Fiber Layer Thickness Analysis Based on Bruch's Membrane Opening

Abstract: PURPOSE.To compare the diagnostic ability of the new spectral-domain optical coherence tomography (SD-OCT) algorithm for measuring circumpapillary retinal nerve fiber layer (RNFL) thickness centered on Bruch's membrane opening (BMO), with the conventional circumpapillary RNFL thickness measurement centered on the optic disc.METHODS. In 75 eyes with primary open-angle glaucoma (POAG) and 71 healthy control eyes, circumpapillary RNFL thickness was measured with SD-OCT, first by centering the scan circle on the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 42 publications
0
28
1
Order By: Relevance
“…37 Defining the optic disc margins based on the BMO as a clear anatomic structure has been suggested to be more reliable and consistent. 2,20,[38][39][40] The APS of the Spectralis SD-OCT defines the optic disc based on the BMO and aligns the OCT scans accordingly. Hence, the discrepant findings between our and previous studies may be explained by our SD-OCT system using the APS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…37 Defining the optic disc margins based on the BMO as a clear anatomic structure has been suggested to be more reliable and consistent. 2,20,[38][39][40] The APS of the Spectralis SD-OCT defines the optic disc based on the BMO and aligns the OCT scans accordingly. Hence, the discrepant findings between our and previous studies may be explained by our SD-OCT system using the APS.…”
Section: Discussionmentioning
confidence: 99%
“…Analyses of RNFLT are frequently used in glaucoma diagnostics [1][2][3] and hold promise as a biomarker for various neurodegenerative diseases. 4,5 Alterations and thinning of different retinal layers have been associated with neurologic diseases such as multiple sclerosis or Parkinson's disease.…”
mentioning
confidence: 99%
“…A recent study has shown that although overall RNFL-BMO measurements have similar ability to detect glaucoma compared to traditional RNFL measurements, RNFL-BMO performed better in eyes with larger width externally oblique border tissue, a feature of titled optic discs. 41 There is however a lack of studies examining the long term reproducibly of RNFL-BMO and its ability to detect progression.…”
Section: What Quantity Of Change Is Significant?mentioning
confidence: 99%
“…Since the majority of structural diagnostic tools used to detect glaucoma are based on ONH evaluation, glaucoma diagnosis is difficult in myopic individuals with ONH deformation. In these patients, BMO-based parameters (e.g., BMO-MRW or BMO-based circumpapillary retinal nerve fiber layer [RNFL] thickness) have been proposed as good alternative diagnostic options 1113 . Lee et al .…”
Section: Introductionmentioning
confidence: 99%